Scenarios, stories, use cases : through the systems development life-cycle - Alexander, Ian (Ian F.), 1954-; Maiden, Neil (Wiley, 2004)
Extending the scenario method beyond interface design, this important book shows developers how to design more effective systems by soliciting, analyzing, and elaborating stories from end-users.